Approaches to the formation of the enterprise development strategy (on the example of furniture production in the Pavlodar region) - Tursynkhanov, D.Zh.; Nurgalieva, S.Zh.; Bekniyazova, D.S. (BUKETOV BUSINESS REVIEW, 2021)
Object: The article considers new approaches to the formation of the company’s development strategy (on the example of furniture production in the Pavlodar region). In particular, the goal of the study is to evaluate the competitive position of the enterprise, based on the use of a spatial model (SPACE model) and the method of expert assessments, taking into account factors of the internal and external environment. Methods: This research adopts the method of expert assessments, including the quantitative and qualitative research methods with a survey data collection technique. The initial data have been collected by a questionnaire with six point scales, it is used SPACE-model which allows to determine the type of development strategy - the most optimal for the enterprise taking into account the parameters of the external and internal environment of the enterprise. Findings: The results show that the company under study is characterized by an average attractiveness of the furniture market in the city of Pavlodar, a stable financial position, which is limited by an unstable external environment. In addition, the company according to the study has aggressive competitive position in the furniture sales market, which entails the potential ability to resist competitors. Conclusion: Based on the results obtained, it is advisable to form and implement a strategy for intensive growth of the studied enterprise, which assumes either a deeper penetration of the enterprise into the existing market with the existing product range or penetration into new markets with the existing range. The authors also recommend the following strategies for intensive growth: 1) the strategy of expanding the market boundaries; 2) the strategy of deep market penetration